Assessing the costs and benefits of water use for production and the potential of water demand management in the Crocodile Catchment of South Africa - Hassan, Rashid M. (University of Pretoria, 2013)
Dissertation (MSc (Agricultural Economics))--University of Pretoria, 2004.